Effect of the Collaborative School Inspection Approach on Teacher Instruc-tional Effectiveness in Government-aided Primary Schools of Nakisunga County, Mukono District, Uganda - Ntege, Joseph Lubwama; Wilson, Kasule George; Mugizi, Wilson; Phillip, Owino (Future Science / FSH-PH Publications, 2023)
The study investigated the effect of the collaborative school inspection approach on teacher instructional effectiveness in government-aided primary schools in Nakisunga County, Mukono district, Uganda. Teacher instructional effectiveness was studied in terms of reporting on pupil academic achievements, teacher attitudes, effective planning, attendance and pedagogical approaches. Collaborative school inspection approaches were studied in terms of support supervision, feedback, trust and respect. The study adopted a cross-sectional survey mixed research design which used both quantitative and qualitative approaches on a sample of 178 people that included teachers, head teachers, school inspectors and education officers, all from Nakisunga County, Mukono district. While Quantitative data was collected using self-administered survey questionnaires, qualitative data was collected using interviews and focus group discussions. Data collected quantitatively was analysed using inferential analysis yet qualitative data was analysed by grouping the responses from the head teachers, school inspectors and education officers in themes which were merged with quantitative findings. The findings showed that all the sub-variables of the collaborative school inspection approach were positively significant to teacher instructional effectiveness. It was concluded that the collaborative school inspection approach has impact, on teacher instructional effectiveness. Therefore, it was recommended that because the collaborative school inspection approach has impact on teacher instructional effectiveness it should be used in government-aided primary school inspection activities always and vigilantly because all its sub-variables were positively significant to teacher instructional effectiveness.